Analisis Variasi RPM Motor Listrik terhadap Variasi Dimensi Produk pada Mesin Pemotong Bakso Kotak - Rohman, Muhamad Nur; Choifin, Mochamad; Herlambang, Bayu (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2025)
In the food industry, the dough cutting process is needed to shape the dough as desired, such as square meatballs. Manual cutting of dough squares is done by cutting vertically and horizontally, but this method is time consuming. Therefore, mowers with electric motors are used for efficiency. Setting motor rpm is very important for optimal cutting results. If the rpm is too fast or slow, the results will not be appropriate. This research aims to find the right rpm range for a box meatball cutting machine. The research method was carried out by directly testing the machine at various conveyor motor rpm variations (2800, 2700, and 2600 rpm) and cutting motor variations (1400, 1350, and 1300 rpm) then measuring the dimensions of the resulting dough pieces. The research results showed that the combination of conveyor motor rpm of 2600 rpm and cutting motor rpm of 1350 rpm gave the best average cutting dimensions with a deviation value of 1 because at that rpm the conveyor and cutting knife had a speed difference that was not that big.